Therapeutic Advances in Pediatric Multiple Sclerosis - Walsh, Rachel; Chitnis, Tanuja (Children (Basel), 2025)
Pediatric-onset multiple sclerosis (POMS) is a chronic, immune-mediated disorder that affects the central nervous system in children and adolescents. Approximately 3–10% of MS patients have an onset that occurs before the age of 18. The vast majority of pediatric MS cases are characterized by a relapsing-remitting course with a high burden of disease activity. Pediatric MS patients were historically treated off-label with varying degrees of success. With the approval of many new therapies for adult-onset MS, alternative treatments in pediatric MS have rapidly started to emerge. In this narrative review, we will discuss therapeutic advancements in pediatric multiple sclerosis, including the seminal trials of PARADIGMS, which evaluated fingolimod use in pediatric MS patients, CONNECT (dimethyl fumarate), TERIKIDS (teriflunomide), OPERETTA I (ocrelizumab), and LEMKIDS (alemtuzumab). We will also review the safety and efficacy of different monoclonal antibodies that are commonly prescribed for multiple sclerosis. We will then examine induction versus escalation treatment strategies and conclude with discussions on treatment considerations in POMS patients.